O aspektualnej naturze konstrukcji am-Progressiv w języku niemieckim i jej znaczeniu w wybranych kontekstach konfrontacji z językiem polskim - Kozyra, Małgorzata (Investigationes Linguisticae, 2010)
The aim of this article is to show the wide aspectual context of the german am-Progressive (sein+am+Infinitiv). The assumption that all languages (in this case particularly German and Polish) are able to express universal meaning-structure of aspectuality allows a contrastive view of German and Polish. The Progressivity will be shown here as a domain of imperfectivity in a universal, prelexical structure of aspectuality. The polish verbal category of the aspect and the german am-Progressiv are both used to express aspectuality, which could be used in teaching German as a foreign language.